2014
DOI: 10.1111/php.12329
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of UV‐B Radiation Intensity on Biochemical Parameters and Active Ingredients in Flowers of Qi Chrysanthemum and Huai Chrysanthemum

Abstract: The article studied UV-B effects on biochemical parameters and active ingredients in flowers of Qi chrysanthemum and Huai chrysanthemum during the bud stage. The experiment included four UV-B radiation levels (CK, ambient UV-B; T1, T2 and T3 indicated a 5%, 10% and 15% increase in ambient UV-BBE, respectively) to determine the optimal UV-B radiation intensity in regulating active ingredients level in flowers of two chrysanthemum varieties. Flower dry weight of two cultivars was not affected by UV-B radiation u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…As a Chinese traditional herb, a large number of cultivars of C. morifolium were gradually evolved, and Huai C. morifolium is one of them, which was widely cultivated in Jiaozuo, Henan province [30]. In the present study, the essential oil was extracted (yield = 0.53% w/w) from Huai C. morifolium flowers.…”
Section: Chemical Composition Of Hceomentioning
confidence: 89%
“…As a Chinese traditional herb, a large number of cultivars of C. morifolium were gradually evolved, and Huai C. morifolium is one of them, which was widely cultivated in Jiaozuo, Henan province [30]. In the present study, the essential oil was extracted (yield = 0.53% w/w) from Huai C. morifolium flowers.…”
Section: Chemical Composition Of Hceomentioning
confidence: 89%
“…In recent years, several studies have reported the use of supplemental UV to alter the chemistry of medicinal chrysanthemum (Chrysanthemum morifolium Ramat) flowers, for which the main active components are flavonoids and chlorogenic acid (Yao et al 2014;Ma et al 2016). Here we showed that supplemental UV radiation can be used to enhance chrysanthemum defenses against an important insect pest during the vegetative stage as well.…”
Section: Discussionmentioning
confidence: 99%
“…Delta 1-pyrroline-5-carboxylate synthetase 2 protein (spot 1468) catalyzes the first two steps of proline biosynthesis in plants [50]. Many studies have proved that proline metabolism is a typical mechanism of biochemical adaptation in living organisms subjected to stressful conditions [51], such as salt stress [52], drought [53] and UV stress [11]. Nucleoside diphosphate kinase (NDPK, spot 1590) is mainly located in the cytoplasm, which catalyzes the transfer of gamma phosphate from ATP to cognate nucleoside diphosphates (NDP) to maintain the balance between cellular ATP and other NTPs [54].…”
Section: Uv-b Effects On Proteomic Changes In Postharvest Flowers Of mentioning
confidence: 99%
“…However, some interesting results about UV-B-beneficial effects on secondary metabolism processes in medicinal plants have been found in recent years [5][6][7][8][9][10][11][12]. Most of medically active ingredients in medicinal plants are secondary metabolites.…”
Section: Introductionmentioning
confidence: 97%